What is new in narrow-band ultraviolet-B therapy for vitiligo? - Urmi Khanna; Sujay Khandpur (Wolters Kluwer Medknow Publications, 2019)
Vitiligo is an acquired disorder of skin pigmentation that produces significant psychological impact especially in those with skin of color. Narrow-band ultraviolet B (NB-UVB) therapy, which was first used in vitiligo in 1997 by Westerhof and Nieuweboer-Krobotova, has emerged as one of the safest and most effective therapy for this dermatosis. The light source used for NB-UVB phototherapy is the TL-01 lamp, and the most common model of the NB-UVB phototherapy device is the upright in-office booth or chamber which has 24-48 such lamps. In recent years, there have been several advances in the understanding of the mechanism of action of NB-UVB and the use of combination treatments, many of which increase the efficacy of NB-UVB. In 2017, the Vitiligo Working Group made vital recommendations on the dosage, frequency, and safety of NB-UVB in vitiligo. Furthermore, home phototherapy devices are gaining popularity as they lead to an improved patient compliance. There is still need for large multicenter randomized controlled trials to assess benefits of home phototherapy in vitiligo and studies investigating additional benefits of phototherapy following surgical therapy.